Genome Partitioning of Genetic Variation for Milk Production and Composition Traits in Holstein Cattle - Pimentel, Eduardo da Cruz Gouveia; Erbe, Malena; Koenig, Sven; Simianer, Henner (Frontiers in Genetics, 2011)
The objective of this study was to estimate the contribution of each autosome to genetic variation of milk yield, fat and protein percentage and somatic cell score in Holstein cattle. Data on 2294 Holstein bulls genotyped for 39’557 autosomal markers were used. Three approaches were applied to the estimation of the proportion of variance attributed to each chromosome. In two of them, marker-derived kinship coefficients were computed, using either marker genotypes observed on the whole genome or on subsets relative to each chromosome. Variance components were then estimated using residual maximum likelihood in method 1 or a regression based approach in method 2. In method 3, genetic variances associated to each marker were estimated in a linear multiple regression approach, and then were summed up chromosome-wise. Generally, all chromosomes contributed to genetic variation. For most of the chromosomes, the amount of variance attributed to a chromosome was found to be proportional to its physical length. Nevertheless, for traits influenced by genes with very large effects a larger proportion of the genetic variance is expected to be associated with the chromosomes where these genes are. This is illustrated with the DGAT1 gene on BTA14 which is known to have a massive effect on fat percentage. The proportion of genetic variance for fat percentage associated with chromosome 14 was 2 to 7 fold (depending on the method) larger than would be predicted from chromosome size alone. Based on method 3 an approach is suggested to estimate the effective number of genes underlying the inheritance of the studied traits, yielding numbers between N=400 (for fat percentage) to N=900 (for milk yield). It is argued that these numbers are conservative lower bound estimates, but are in line with recent findings suggesting a highly polygenic background of production traits in dairy cattle.